Structural Model of the IDX Credibility - Wintoro, Djoko (UI Scholars Hub, 2009)
Indonesia Stock Exchange (IDX) needs to increase its credibility for the purpose of increasing favorable investment environment for both domestic and foreign investors. The perception of stockbrokers is used to develop structural model of the IDX credibility as measured by stock trading volume and frequency. Factor analysis overview has found three important group regulations: stock trading services, stock trading protection, and stock trading efficiency - which are influent to the credibility of IDX. Structural equation modeling analysis confirms that those three group regulations positively influence the credibility of IDX.